Clinically-Endoscopic Manifestations of Peptic Ulcer disease in Children Depending on Helicobacter pylori Infection - Т.V. Sorokman; S.V. Sokolonyk; М.G. Gingulyak; N.О. Popelyuk (Zaslavsky O.Yu., 2014)
We analyzed the clinical and endoscopic features of H.pylori-associated peptic ulcer disease in children. Prevalence of H.pylori-positive cases of peptic ulcer disease, regardless of the localization of ulcers, was determined. Toxigenic strains of H.pylori cause severe course of ulcer disease with prolonged and frequent relapses. Most of H.pylori-positive lesions are associated with Cag+-VacA+ serotype of microorganism. In individuals infected with serotype CagA-VacA+, ulcers of large sizes are more common.